2013
DOI: 10.1371/journal.pone.0074068
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status in Type 1 Diabetic Pregnancy: Impact on Neonatal Vitamin D Status and Association with Maternal Glycaemic Control

Abstract: ObjectiveThe first aim of this study was to assess 25-hydroxy vitamin D (25OHD) concentrations in women with type 1 diabetes (T1DM) during pregnancy, post-delivery and also foetal (cord blood) 25OHD concentrations and to examine relationships between these. The second aim of the study was to investigate potential interactions between maternal body mass index (BMI) and foetal vitamin D status. A further study aim was to examine potential relationships between maternal 25OHD and glycosylated haemoglobin (HbA1c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The concentration of 25(OH)D is relatively constant throughout pregnancy [ 6 ]. The mother is the only source of vitamin D for the foetus [ 7 ]. Vitamin D concentrations in the umbilical cord are usually 60–89% of the values in the mother’s blood.…”
Section: Physiology Of Vitamin D During Pregnancymentioning
confidence: 99%
“…The concentration of 25(OH)D is relatively constant throughout pregnancy [ 6 ]. The mother is the only source of vitamin D for the foetus [ 7 ]. Vitamin D concentrations in the umbilical cord are usually 60–89% of the values in the mother’s blood.…”
Section: Physiology Of Vitamin D During Pregnancymentioning
confidence: 99%
“…Reported associations of vitamin D deficiency in diabetic pregnancy include preterm birth, increased T1DM rates in offspring of women with T1DM, and poor glycaemic control. 11,16,19,20,23 Some studies of non-diabetic pregnant women have suggested associations between low total 25(OH)D and contemporaneous 9 or subsequent PE, 8,11 perhaps limited to early-onset disease. 12 Our present finding of no significant association is consistent with our previous study (that used different methodology to measure 25(OH)D), 24 and with a study by Vestgaard et al .. 16 The present work extends those findings by showing that, like total 25(OH)D, neither bioavailable nor free forms of 25(OH)D were predictive of PE.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, 25(OH)D, the standard metric for vitamin D, did not predict PE; of note, however, insufficient or deficient levels were almost universal in our diabetic cohort. Reported associations of vitamin D deficiency in diabetic pregnancy include preterm birth, increased T1DM rates in offspring of women with T1DM, and poor glycemic control [12,17,20,21,29]. Some studies in non-diabetic pregnant women have suggested that low total 25(OH)D is associated with contemporaneous [10] or subsequent PE [9,12], perhaps limited to early-onset disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…Women with type 1 diabetes (T1DM) have a markedly increased risk for PE (~20% vs.~5% in the general population) [28]. Vitamin D deficiency is associated with abnormal placentation, altered angiogenesis, immune dysfunction, abnormal insulin secretion and action, adverse lipid profiles, and inflammation: problems that are also associated with diabetes [2,4,11,[13][14][15][16][17]19,29]. Vitamin D deficiency may also be implicated in PE [9,13].…”
Section: Introductionmentioning
confidence: 99%